2022
DOI: 10.1371/journal.pone.0261513
|View full text |Cite
|
Sign up to set email alerts
|

Does simultaneous soft tissue augmentation around immediate or delayed dental implant placement using sub-epithelial connective tissue graft provide better outcomes compared to other treatment options? A systematic review and meta-analysis

Abstract: Objective The clinical benefits of simultaneous implant placement and soft tissue augmentation using different treatment modalities are unclear. The current meta-analysis aimed to compare the effect of simultaneous soft tissue augmentation using subepithelial connective tissue graft (SCTG) around immediate or delayed dental implant placement with other treatment modalities on the peri-implant tissue health and esthetic. Methods Up to May 2021, four databases (PubMed, EMBASE, Cochrane Central, and Google Scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 54 publications
2
10
0
2
Order By: Relevance
“…36,37 Regarding the change in mucosal thickness from baseline after 12 months, the SCTGG showed a statistically significant increase of 1.5 (0.4) mm. This is in line with the findings reported by Aldhohrah and colleagues 15 who observed an average gain in BTT, over 12 months, of 1.3 mm with SCTG in delayed implant placement. More interestingly, the NGG from baseline showed a 0.4 (0.2) mm gain in BTT which could be attributed to the design of the immediate provisional restoration that led to the formation of a space between the implant restoration and the peri-implant mucosal tissues that was filled with a clot in the subcritical contour contributing to soft tissue thickening.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…36,37 Regarding the change in mucosal thickness from baseline after 12 months, the SCTGG showed a statistically significant increase of 1.5 (0.4) mm. This is in line with the findings reported by Aldhohrah and colleagues 15 who observed an average gain in BTT, over 12 months, of 1.3 mm with SCTG in delayed implant placement. More interestingly, the NGG from baseline showed a 0.4 (0.2) mm gain in BTT which could be attributed to the design of the immediate provisional restoration that led to the formation of a space between the implant restoration and the peri-implant mucosal tissues that was filled with a clot in the subcritical contour contributing to soft tissue thickening.…”
Section: Discussionsupporting
confidence: 93%
“…23,24 Nevertheless, there is a paucity of studies on immediate provisionalization and its effect on the esthetics around delayed implants. 14 Moreover, in a recent systematic review, 15 T A B L E 4 Buccal peri-implant soft tissue thickness (mm) in both groups at baseline (TP), after 6 (T1), and 12 months (T2) concluded that there is still a lack of clear evidence regarding the benefits of SCTG around delayed implants from a clinical and esthetic point of view. Hence, the aim of the current study was to assess whether immediate provisionalization without soft tissue augmentation could lead to a comparable peri-implant soft tissue esthetic score when compared to soft tissue augmentation combined with immediate provisionalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone grafting has compensated for soft‐ and hard‐tissue collapse (Mao et al, 2021; Tarnow et al, 2014). However, the benefits of using autologous tissue grafts or alternative materials, such as a collagen matrix or acellular dermal matrix (ADM), combined with immediate implantation are equivocal (Aldhohrah et al, 2022; Jung et al, 2022). A thick mucosal phenotype is associated with more stable peri‐implant bone levels and dimensions than a thin mucosal phenotype, as demonstrated in several preclinical (Berglundh & Lindhe, 1996) and clinical studies (Linkevicius et al, 2009; Vervaeke et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In the past, delayed implantation (DI) was mostly used; that is, implantation was accomplished 3 to 6 months after tooth extraction when the tooth extraction site was completely healed and the bone reconstruction was basically stable, so that the implant could form bony union after implantation with favorable safety [ 2 ]. However, this implant procedure will result in a protracted period of tooth loss, as well as keratinization of the gums and insufficient bone mass in the edentulous area due to alveolar bone absorption following tooth extraction, which will impact the aesthetic effect of implant repair [ 3 , 4 ]. With the advances in stomatology, immediate implantation (II) technology has attracted the attention of stomatologists at home and abroad, as it not only shortens the number of surgical interventions and simplifies the treatment procedures but also preserves the soft tissue capsule to achieve the best soft tissue aesthetics [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%